The influence of structure and morphology on ion permeation in commercial silicone hydrogel contact lenses. Issue 1 (24th July 2020) - Saez‐Martinez, Virginia; Mann, Aisling; Lydon, Fiona; Molock, Frank; Layton, Siân A.; Toolan, Daniel T. W.; Howse, Jonathan R.; Topham, Paul D.; Tighe, Brian J.
Abstract: The importance of the microstzructure of silicone hydrogels is widely appreciated but is poorly understood and minimally investigated. To ensure comfort and eye health, these materials must simultaneously exhibit both high oxygen and high water permeability. In contrast with most conventional hydrogels, the water content and water structuring within silicone hydrogels cannot be solely used to predict permeability. The materials achieve these opposing requirements based on a composite of nanoscale domains of oxygen‐permeable (silicone) and water‐permeable hydrophilic components. This study correlated characteristic ion permeation coefficients of a selection of commercially available silicone hydrogel contact lenses with their morphological structure and chemical composition. Differential scanning calorimetry measured the water structuring properties through subdivision of the freezing water component into polymer‐associated water (loosely bound to the polymer matrix) and ice‐like water (unimpeded with a melting point close to that of pure water). Small‐angle x‐ray scattering, and environmental scanning electron microscopy techniques were used to investigate the structural morphology of the materials over a range of length scales. Significant, and previously unrecognized, differences in morphology between individual materials at nanometer length scales were determined; this will aid the design and performance of the next generation of ocular biomaterials, capable of maintaining ocular homeostasis.